A study on the effects of light intensity on juveniles of the red claw crayfish Cherax quadricarinatus. (23rd September 2022) - Wen‐ping, Jiang; Shun, Cheng; Yong‐yi, Jia; Mei‐li, Chi; Shi‐li, Liu; Jian‐bo, Zheng; Fei, Li; Yi‐nuo, Liu; Zhi‐min, Gu; Dan‐li, Wang
Abstract: To study the effect of light intensity on red claw crayfish juveniles, experiments were carried out in this study. The results showed the following. (1) The 20 lux group had the highest survival rate. (2) The growth rates of the 20 lux, 200 lux and 0 lux groups were faster. (3) The juveniles in the 1000 lux and natural light groups were always clustered, while other groups were dispersed within 2–3 days. The 0 lux and 20 lux groups had higher dispersion. (4) Antioxidant capacities in the 0 lux and 20 lux groups were higher, and immune capacity in the 20 lux group was higher. (5) Monoamine contents were lower in the 0 lux and 20 lux groups. (6) α‐AMY or EcR expression in the 20 lux or 0 lux group was higher. We concluded that (1) juveniles under 20 lux light intensity had higher survival and growth rates. (2) The dispersion of juveniles at 0 lux and 20 lux light intensity was higher. (3) The physiological metabolism and immune abilities of juveniles at 0 lux and 20 lux light intensity were higher. (4) 0 lux and 20 lux was helpful in inhibiting cannibalism. (5) A 20 lux light intensity was helpful to in the expression of α‐AMY to improve digestion and absorption capacity. Low‐intensity light enhanced the expression of EcR, which contributed to the moulting of juveniles. We considered in actual production, it could be necessary to control 20 lux light intensity during the intermediate cultivation period of juveniles.